Early Lives of Charlemagne by Eginhard and the Monk of St Gall edited by Prof. A. J. Grant - Einhard, 770?-840; Notker, Balbulus, 840?-912; Grant, A. J. (Arthur James), 1862-1948 (Salt Lake City, UT : Project Gutenberg, 2015)
"Early Lives of Charlemagne" by Eginhard and the Monk of St Gall, edited by Prof. A. J. Grant, is a historical account written in the early 20th century. This work presents two distinct biographies of Charlemagne, exploring his legendary life and reign through the contrasting narratives of Eginhard, who provides a factual and concise account, and the Monk of St Gall, who leans heavily on myth and embellishment. The topic of the book focuses on the life and achievements of Charlemagne, who is known for uniting much of Western Europe during the early Middle Ages and for his role in the Carolingian Renaissance. The beginning of the text introduces the reader to the landscape of historical accounts surrounding Charlemagne, particularly delineating the differences between Eginhard's more straightforward narrative and the Monk of St Gall's more fanciful retelling. It discusses the context of their compositions, touching on their motivations and proximity to Charlemagne, as well as the challenges they faced in documenting a life that soon became shrouded in legend. Eginhard is specifically noted for his intimate knowledge of Charlemagne, having been a close associate, while the Monk's account reveals the mythologizing tendencies that took hold following the emperor's death. The opening establishes the importance of these texts for understanding both the historical figure of Charlemagne and the evolution of his legacy in medieval thought. (This is an automatically generated summary.)
Release date is 2015-05-03
Produced by Andrew Dunning
Keywords: Charlemagne, Emperor, 742-814; France -- Kings and rulers -- Biography; Holy Roman Empire -- Kings and rulers -- Biography; France -- History -- To 987 -- Sources; Holy Roman Empire -- History -- To 1517 -- Sources